ANALISIS PENGARUH HARGA, DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA TOKO BANGUNAN PELITA MAS DI KOTA PALEMBANG - Dharmawan, Vincentius Fernando; Megawati, Megawati (Publikasi Riset Mahasiswa Manajemen, 2024)
This research was conducted to see the role of Price and Location on Consumer Satisfaction at Pelita Mas Building Shop Customers, Palembang City, to find out whether Price and Location partially influence Customer Satisfaction at Pelita Mas Building Shop Customers, Palembang City, and to find out whether Price and Location have an effect on Simultaneous Customer Satisfaction of Pelita Mas Building Shop Customers, Palembang City. The results of this research show that the partial test (t-test) of the Price variable (X1) and Location variable (X2) has a positive and significant effect on consumer satisfaction. The test simultaneously proves that the independent variables, namely the price variable (X1) and the location variable (X2), have an effect on the dependent variable in the form of customer satisfaction (Y).